2023
DOI: 10.1210/endocr/bqad012
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-based Proteomic Analysis Unveils ACSL4 as a Novel Potential Regulator of Human Endometrial Receptivity

Abstract: Competent endometrial receptivity is a prerequisite for successful embryo implantation. Identification of novel key molecules involved in endometrial receptivity is essential to better interpret human implantation and improve pregnancy rates in assisted reproduction treatment. The iTRAQ-based proteomics was performed to profile the proteomes of the prereceptive (LH + 2, n = 4) and receptive (LH + 7, n = 4) endometrial tissues. One hundred seventy-three differentially expressed proteins (DEPs) between LH + 2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…A recent iTRAQ-based proteomics study identified PLA2G4F as a differentially expressed protein (DEPs) in mid-secretory endometrium. It is categorized as one of the top 5 hub proteins that regulate endometrial receptivity [38]. Ceruloplasmin (CP) is the sole gene with down-regulated expression in the LP phase and upregulated expression in the MS phase.…”
Section: Discussionmentioning
confidence: 99%
“…A recent iTRAQ-based proteomics study identified PLA2G4F as a differentially expressed protein (DEPs) in mid-secretory endometrium. It is categorized as one of the top 5 hub proteins that regulate endometrial receptivity [38]. Ceruloplasmin (CP) is the sole gene with down-regulated expression in the LP phase and upregulated expression in the MS phase.…”
Section: Discussionmentioning
confidence: 99%
“…A recent iTRAQ-based proteomics study identified PLA2G4F as a differentially expressed protein (DEP) in mid-secretory endometrium. It is categorized as one of the top five hub proteins that regulate endometrial receptivity [31]. Ceruloplasmin (CP) is the sole gene with downregulated expression in the LP phase and upregulated expression in the MS phase.…”
Section: Discussionmentioning
confidence: 99%